Draft Annual Plan 1971-72 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1971)
Uttar Pradesh is the most heavy populated State in the country, characterised by an undiversified economy, low growth rate, heavy population pressure and high unemployment rate. the industrial base is limited. Almost one-half of the population lives in economically backward areas. If we take a look at tire important indicators the situation becomes quite clear.
Government of Uttar Pradesh, Planning Department